Studying Physical Educator Manual Reality Using SWOT from Secondary School Teachers’ Point of View in Baghdad - Ibrahim, Zina; Shaker, Salah (Journal of Physical Education, 2020)
The research aimed at designing a SWOT questionnaire for physical educators’’ manual as well as identifying the reality of this manual. The researchers used the descriptive method. The subjects were (458) secondary school physical educators in Baghdad. The researchers applied a questionnaire following Likert method for measurement by designing the items of the questionnaire depending on school realities through personal interview and field visits. The researchers designed (89) items to conclude weaknesses and threats after SWOT analyses of the manual. Finally they recommended holding awareness and special educational courses to guide physical educators about the manual as well as benefiting from this research’s results to modify physical educators’’ manual. In addition to that, the researchers recommended making annual evaluation for physical educators and physical education class for improvement and development.